Analysis of Century Old Beer- Chemical, Sensoria! and Genetic Profile of 100-Year-Old Beer - Olšovská, Jana; Matoulková, Dagmar; Felsberg, Jurgen; Jelínková, Markéta; Dušek, Martin; Čejka, Pavel; Štěrba, Karel (KVASNY PRUMYSL, 2016)
Three bottles of different beers were found in 2015 during a reconstruction of the brewery of the Raven Trading s.r.o. company in Záhlinice, Czech Republic. Good storage conditions enabled analysis of their original characteristics. Ali three bottles contained most probably lager type beer. First beer (bright, original extract 10.3%) had sulfuric and fecal off-flavors. The second beer (dark, original extract 7.6 %) was very acidic, resembling Lambic beer. DNA analysis proved the presence of lager yeast Saccharomyces pastorianus and contaminant Dekkera bruxelfensis. The third beer (light brown, original extract 10.4%) contained small C02 bubbles and was slightly bitter. As a consequence of natural aging process the extremely high concentration of 2-turfural was found. The relatively high degree of adjuncts addition could be assumed based on high concentration of myristic acid and simultaneously low concentration of silica. DNA of contaminating microorganisms in all samples was proved.